In conversation W.V. Quine. (Philosophy International, 1994)
Professor Quine defends his critic of modality in this program and provides an explanation of his characterization of logic. He presents his ontological stance and discusses his view of, and his association with, the historical development of logic. He discusses his view of Tarski's famous work on truth, and his prescription for how much logic the philosopher should be aware of.